Positive Politeness Strategies in “All the Bright Places” Movie - Ni Made Budiartini; Ni Made Suwari Antari; Ni Wayan Sukarini (Pusat riset dan Inovasi Nasional, 2025)
This research explores positive politeness strategies in the 2020 film All the Bright Places by analyzing the characters' dialogue. It is based on Brown and Levinson's (1987) theory of positive politeness, supported by Halliday and Hasan's (1989) context of situation framework. Using a qualitative descriptive method, the study analyzes the film script. Data is collected through documentation, including note-taking and recording techniques, to identify relevant utterances. The findings show that fourteen out of fifteen positive politeness strategies from Brown and Levinson's theory appear in the film. Strategy 4, which uses in-group identity markers, is the most common. The characters often try to build solidarity and emotional connection. Other frequently used strategies include noticing the listener, offering or promising, and seeking agreement. These strategies reflect the characters' efforts to build and maintain relationships, show empathy, and manage social interactions. The study concludes that positive politeness strategies are essential in shaping the film's interpersonal relationships and emotional development. Overall, the research highlights how language use in film reflects psychological and social aspects of communication, offering insights into the role of pragmatics in fictional narratives.